Kebijakan Pemerintah Brunei Darussalam Meratifikasi The WHO Framework Convention on Tobacco Control - Hardi Alunaza SD (Dauliyah Journal of Islamic and International Affairs, 2016)
Health issue is one of national priority issue in Brunei in recent decades. Sultan of Brunei formed the seriousness of the health accord with the realization of the national development agenda Health Promotion Blueprint 2011-2015 and the Brunei Vision 2035. This paper is aims to answer the question why Brunei ratified the WHO Convention on Tobacco Control. This paper is an explanatory with qualitative approach. Data collection method in this research is through library with secondary data sources. All data are taken from books, journals, internet articles and other relevant data to the research. By using the theory of the rational actor model of decision making and the concept of health security, this research shows the policy taken by the Sultan of Brunei is a form of the Health Security of Government to the citizens. Sultan of Brunei ratified the WHO Framework Convention on Tobacco Control because of health issue is including in national development agenda. Various efforts to create Brunei Darussalam as a free smoke state in 2025 have been realized. The evidence of the successes policy of Brunei Government related to tobacco control shown by activities of imported tobacco is significantly decreased and also decreasing the number of smokers in Brunei in 2011. It was also offset by the increasing level of public health in Brunei and the achievement of some of WHO health targets as the Millennium Development Goals.